1971
DOI: 10.1037/h0031205
|View full text |Cite
|
Sign up to set email alerts
|

Human partial reinforcement extinction effects: An information processing development from Capaldi's sequential theory.

Abstract: A series of experiments was designed to evaluate the applicability of Capaldi's sequential hypothesis for describing human partial reinforcement-extinction effects (PREEs). The 5s were required to make a decision about whether or not to gamble on an uncertain outcome. Experiment I was designed to determine whether the experimental context would result in a usual PREE. Experiment II evaluated the memory trace assumptions of the theory via the use of intertrial reinforcements. The third, fourth, and fifth experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0

Year Published

1975
1975
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
2
17
0
Order By: Relevance
“…Most investigations of the PREE manipulated the percentage of reinforced responses or trials during acquisition and demonstrated that resistance was inversely related to these percentages. However, results of studies with both humans and nonhumans, conducted primarily by Capaldi and colleagues, suggest that resistance to extinction is determined by other factors related to reinforcement schedules, such as the number of consecutive nonreinforced trials preceding a reinforced trial (N length), the number of different N lengths, and the number of each N length (e.g., Capaldi, 1964;Halpern & Poon, 1971;Litchfield & Duerfeldt, 1969;Meyers & Capaldi, 1970). In addition, the PREE is more likely to occur when PRF is combined with other variables, including lengthy acquisition training (Uhl & Young, 1967), large reinforcement magnitudes (Amsel, Hug, & Surridge, 1968), delayed reinforcement (L. Peterson, 1956), and massed acquisition trials (Sheffield, 1949).…”
Section: Basic (Nonclinical) Researchmentioning
confidence: 99%
“…Most investigations of the PREE manipulated the percentage of reinforced responses or trials during acquisition and demonstrated that resistance was inversely related to these percentages. However, results of studies with both humans and nonhumans, conducted primarily by Capaldi and colleagues, suggest that resistance to extinction is determined by other factors related to reinforcement schedules, such as the number of consecutive nonreinforced trials preceding a reinforced trial (N length), the number of different N lengths, and the number of each N length (e.g., Capaldi, 1964;Halpern & Poon, 1971;Litchfield & Duerfeldt, 1969;Meyers & Capaldi, 1970). In addition, the PREE is more likely to occur when PRF is combined with other variables, including lengthy acquisition training (Uhl & Young, 1967), large reinforcement magnitudes (Amsel, Hug, & Surridge, 1968), delayed reinforcement (L. Peterson, 1956), and massed acquisition trials (Sheffield, 1949).…”
Section: Basic (Nonclinical) Researchmentioning
confidence: 99%
“…Previous studies of human infant learning, however, have not looked for partial reinforcement effects or extinction bursts. In contrast, partial reinforcement effects are robust in adults and have been demonstrated in a variety of tasks (see review by Halpern & Poon, 1971). For example, when adults learn to move a joystick in one of four directions to receive reinforcement, they persist longer when trained under conditions of partial reinforcement (Pittenger & Pavlik, 1988).…”
mentioning
confidence: 99%
“…When subjects are given relatively extended training (i.e., when asymptotic habit strength is reached), N-Iength is more frequently the major determiner of resistance to extinction. This prediction was supported by Halpern and Poon (1971) using extended training, but no continuous reinforcement control group was included. The first study reported below gave subjects extended training (26 trials) with two different 50% reinforcement schedules.…”
mentioning
confidence: 84%
“…In the first study, it was anticipated that extended acquisition training would cause the reinforcement schedule with the longer N-Iength to produce greater resistance to extinction, as one would expect given Halpern and Poon's (1971) results. Although the schedule with the longer N-Iengths did produce greater resistance to extinction, the results failed to show any partial reinforcement effect for the group that received short N-Iengths coupled with many N-R transitions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation